2022
DOI: 10.1002/ptr.7490
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulated by microbiota‐derived hydrogen sulfide mediates the regulation of berberine on microglia in transient middle cerebral artery occlusion rats

Abstract: Amelioration of neuroinflammation via modulating microglia is a promising approach for cerebral ischemia therapy. The aim of the present study was to explore gut–brain axis signals in berberine‐modulating microglia polarization following cerebral ischemia. The potential pathway was determined through analyzing the activation of the vagus nerve, hydrogen sulfide (H2S) metabolism, and cysteine persulfides of transient receptor potential vanilloid 1 (TRPV1) receptor. The cerebral microenvironment feature was expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Huangqi-Honghua (Wang K. et al, 2022) Ruminococcaceae, Bacteroides, Phascolarctobacterium, Desulfovibrionaceae↓ Blautia, Lachnospiraceae, Oscillibacter, Bifidobacterium↑ bile acid receptor FXR activated Huazhuo Jiedu Huoxue Tongluo Prescription (Ni et al, 2022) Firmicutes, Bacteroidetes, Lactobacillus, Prevotella↑ Enterobacteriaceae, Clostridium, Enterococcus↓…”
Section: Tcm Prescriptionmentioning
confidence: 99%
“…Huangqi-Honghua (Wang K. et al, 2022) Ruminococcaceae, Bacteroides, Phascolarctobacterium, Desulfovibrionaceae↓ Blautia, Lachnospiraceae, Oscillibacter, Bifidobacterium↑ bile acid receptor FXR activated Huazhuo Jiedu Huoxue Tongluo Prescription (Ni et al, 2022) Firmicutes, Bacteroidetes, Lactobacillus, Prevotella↑ Enterobacteriaceae, Clostridium, Enterococcus↓…”
Section: Tcm Prescriptionmentioning
confidence: 99%
“…Finally, a recent study suggested an indirect link between H 2 S and sphingolipids in a rat model of cerebral ischemia. In that study, the authors orally applied berberine to ischemic rats which improved the neuroinflammation and disease scores in tMCAO-induced cerebral ischemia [ 167 ]. It was shown that oral berberine acted on the gut microbiota and stimulated H 2 S production in the intestine, which subsequently activated the vagus nerve to subsequently alter the cerebral microenvironment resulting in less microglia activation and reduced neuroinflammation.…”
Section: Cross-regulation Of Redox and Sphingolipid Signallingmentioning
confidence: 99%
“…Metabolomics analysis of various brain regions revealed changes in sphingolipid metabolism which may mediate the neuroprotection following vagus nerve activation. Notably, sphingosine was strongly increased in the ischemic rat cortex and downregulated by berberine treatment [ 167 ]. These data suggest that microbiota H 2 S production affects cerebral sphingolipid metabolism through vagus nerve activation.…”
Section: Cross-regulation Of Redox and Sphingolipid Signallingmentioning
confidence: 99%
“…In line with this observation, in a rat model of transient ischemia, berberine, an alkaloid with weak antibiotic properties, decreased CD86-positive and increased CD163-positive microglial cells in the cerebral cortex, in a microbiota-dependent manner. The authors show that the hydrogen sulfide (H 2 S) derived from microbiota metabolization of berberine, stimulates the vagus nerve through the transient receptor potential vanilloid 1 (TRPV1) and that a cocktail of antibiotics blocked vagal activation, confirming the necessity of a functional metabolizing microbiota ( 128 ).…”
Section: Gut Microbiota-derived Molecules Controlling Microglia In He...mentioning
confidence: 99%